ADVANTAGES OF TEACHING RUSSIAN LANGUAGE TO STUDENTS OF THE FOOD SCIENCE DEPARTMENT OF A TECHNICAL UNIVERSITY BASED ON TERMINOLOGY (TAMADDUN NURI JURNALI, 2025)
This article is devoted to studying the advantages of teaching Russian to students of food specialties of technical universities based on terminology. The article discusses the importance of mastering the terminology used in the professional sphere, in particular, in the food industry, its role in improving students' professional competencies and its benefits in international cooperation. It also analyzes the impact of this approach on the educational process and the added value of students' future activities. The article is useful for teachers, students and education specialists, and offers effective methods of terminological teaching.